ANALISIS FAKTOR-FAKTOR DOMINAN YANG MEMPENGARUHI EKONOMI RUMAHTANGGA PETANI PADI SAWAH DI KECAMATAN SUNGAI MANDAU KABUPATEN SIAK - Suci Jamilah; Suardi Tarumun; Djaimi Bakce (DINAMIKA PERTANIAN, 2018)
This research aims to analyze the dominant factors that respect to household economics of paddy farmers that included production, allocation of work time, income, and expenditure in Sungai Mandau Sub-district, Siak Municipality. The econometric approach using a model of simultaneous equations with Two-Stage Least Square method (2SLS) was used to answer the research goals. The main finding of this research showed that the dominant factors that respect to production are harvest area of paddy and costs of production facilities. Allocation of work time consists of: First, allocation of work time on farming respects the allocation of work time of off-farm and labor force. Second, the hired labor respects to farming income. Third, allocation of work time of off-farm respects to off-farm income, allocation of work time on farming, farmer's work experiences and age of farmers. Income respects to the allocation of work time of off-farm. Expenditure consists of: First, food consumption respects to total income, the number of families, and health spending. Second, non-food consumption respects to total income. Third, education investment respects to total income and the number of school children. Fourth, paddy farming investment respects to total income, harvest area of paddy, and food consumption. Fifth, saving respects to total income, total consumption, education investment, and health spending.